2002
DOI: 10.1253/circj.66.453
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Ventilatory Response During Exercise in Patients With Non-Hypoxic Pulmonary Hypertension.

Abstract: e can evaluate exercise capacity by oxygen consumption (V • O2), carbon dioxide output (V • CO2) and minute ventilation (V • E), [1][2][3][4] and the slope of the linear regression line between V• CO2 and V • E (SLOPE) is a useful parameter for indicating exercise capacity in chronic heart failure patients. [5][6][7][8][9] Furthermore, SLOPE is an index of ventilatory -perfusion inequality. 6,9 Few studies have investigated the relationship between exercise capacity and SLOPE in patients with pulmonary hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…Mitani et al [25] suggested that it is necessary – when performing a CPET in PAH patients – to observe not only VO2 or VCO2, but also Ve/VCO2, in order to prevent aggravation of the ventilation/perfusion inequality, which leads to exercise-induced hypoxemia. A higher VE/VCO2 ratio describes a greater ventilatory requirement for eliminating the CO2 produced by aerobic metabolism and defines a reduced ventilatory efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitani et al [25] suggested that it is necessary – when performing a CPET in PAH patients – to observe not only VO2 or VCO2, but also Ve/VCO2, in order to prevent aggravation of the ventilation/perfusion inequality, which leads to exercise-induced hypoxemia. A higher VE/VCO2 ratio describes a greater ventilatory requirement for eliminating the CO2 produced by aerobic metabolism and defines a reduced ventilatory efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…If a simple non-invasive measurement, such as the VE/VCO2 ratio, could be shown to be useful in evaluating pulmonary vascular disease, it might serve to supplement other methods currently used to monitor clinical course and treatment. At now, few studies have investigated the relationship between exercise capacity and VE/VCO2 slope in patients with PH [24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…The minimum dataset collected during exercise includes V E , oxygen and carbon dioxide content of inspired and expired air, HR and oxygen saturation (S p O 2 ). With these measurements the characteristic pathophysiological response of PAH patients can be seen, i.e., profound exercise limitation marked by impairment of oxygen transport and inefficient gas exchange with very high ventilatory demand [77][78][79][80][81][82][83][84][85]. In an incremental CPET, the oxygen transport abnormality is reflected in a low VO 2 at anaerobic threshold, low VO 2 -workrate slope, low peak oxygen (O 2 ) pulse (defined as the ratio of peak VO 2 to peak HR) and a steep HR-VO 2 response, combined on occasions with a HR response which fails to reach predicted maximum.…”
Section: Cardiopulmonary Exercise Testingmentioning
confidence: 99%
“…Im Vergleich zwischen PHT-Patienten (n = 8) und solchen mit CHF bei Zustand nach Herzinfarkt (n = 38) wurde für die PHT-Patienten eine deutlich schlechtere Atemeffizienz bei vergleichbarer Peak-VO 2 nachgewiesen [33]. Mittels des zeitlichen Verhaltens unter Belastung (z.B.…”
Section: Belastungsuntersuchungenunclassified